2015
DOI: 10.1177/0276236615587493
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Imagined Interactions With Pro-Ana (Anorexia)

Abstract: For individuals suffering from an eating disorder, the Internet is a place of encouragement and support. To date, however, no comprehensive research has been done to examine particular entries on blogs used by those individuals. Therefore, this study aimed to fill that gap. It focuses on what types of messages individuals communicate to pro-anorexia (Pro-Ana) website and what types of imagined interactions they have with others about their disorder. A total of 587 Pro-Ana blog entries were content analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Those with AN may also engage in fantasies of believing themselves to be thinner, thus enabling them a temporary feeling of thinness (Myers & Biocca, 1992). Some evidence has shown that those with AN may even imagine interacting with their AN as a positive partnership (Mulveen & Hepworth, 2006; Sheldon, Grey, Vickery, & Honeycutt, 2015). Finally, work examining the role of media in AN has indicated that media displays of thinness can be used in rituals involving comparison wherein women display thin images from media as a way of motivating themselves to attain a specific, idealized appearance (Hermes, 1995; Thomsen et al, 2001).…”
Section: Hypothesis 2: Cognitive Amplifiers Of Positive Emotion In Anmentioning
confidence: 99%
“…Those with AN may also engage in fantasies of believing themselves to be thinner, thus enabling them a temporary feeling of thinness (Myers & Biocca, 1992). Some evidence has shown that those with AN may even imagine interacting with their AN as a positive partnership (Mulveen & Hepworth, 2006; Sheldon, Grey, Vickery, & Honeycutt, 2015). Finally, work examining the role of media in AN has indicated that media displays of thinness can be used in rituals involving comparison wherein women display thin images from media as a way of motivating themselves to attain a specific, idealized appearance (Hermes, 1995; Thomsen et al, 2001).…”
Section: Hypothesis 2: Cognitive Amplifiers Of Positive Emotion In Anmentioning
confidence: 99%
“…Intrapersonal communication is the foundation to all other types of communication, and embedded in the hierarchy of interpersonal, small group, organization, societal, cultural, or mass communication (Honeycutt, 2015). The breadth of II scholarship has primarily investigated interpersonal interactions; however, several scholars have explored IIs in family (Rosenblatt & Meyer, 1986), health (Sheldon et al, 2015), intercultural (McCann & Honeycutt, 2006), and instructional contexts (Choi et al, 2015). IIs must be contextualized for domain specific communication.…”
Section: Public Speaking Contextsmentioning
confidence: 99%
“…The imagination allows for cognitive scripts that provide communicators with the ability for verbal and/or visual representations of past or anticipated communication behaviors. Verbal imagery involves imagining the dialogue, conversation, or message content, whereas visual imagery involves setting the scene and seeing the interaction (Sheldon et al., 2015). Verbal-only IIs are perceived as more emotionally intense and less similar to actual communication than mixed-imagery interactions; although fewer in frequency, IIs that incorporate visual imagery were perceived as more pleasant (Zagacki et al., 1992).…”
Section: Imagined Interaction (Ii)mentioning
confidence: 99%
“…Although some websites are dedicated to pro‐ana, several social networking websites also contain pro‐ana content, such as Twitter, Tumblr and Facebook (Branley & Covey, 2017; Juarascio et al., 2010). Common features of pro‐ana communities include the following: emotional and motivational support amongst users (especially support to lose weight), ‘thinspiration’ or ‘thinspo’ (inspiration to lose weight, particularly through images of thin, objectified women) and sharing tips to continue weight loss via eating disorder (ED) behaviours (Borzekowski et al., 2010; Ging, 2020; Juarascio et al., 2010; Sheldon et al., 2015; Talbot et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, most research into pro‐ana analyses online content—potentially due to its public availability. This has illuminated the patterns of posts and interactions amongst pro‐ana users (Juarascio et al., 2010; Lai et al., 2021; Sheldon et al., 2015; Tong et al., 2013). Nonetheless, considering how desirable behaviours are constructed within online pro‐ana communities (Haas et al., 2010; Yeshua‐Katz, 2015), it is possible these posts are created to gain status in these communities.…”
Section: Introductionmentioning
confidence: 99%